Advanced GIS and crime analysis: violence against women in West Bengal, India - Biswas, Priyanka (Routledge, 2024)
"Advanced GIS and Crime Analysis explores the existing spatial variability of crime committed against women in West Bengal and steadily excavates the underlying determinants accountable for specific crimes against women. The book applies GIS technologies to visualize complex crime patterns over space and suggests specific measures to curb oppression. The book applies statistical methods and GIS techniques to visualize the vulnerable areas of crime against women in West Bengal and critically discusses emerging criminogenic issues with respect to theoretical understanding and immediate situations. The determination of the most significant crime hotspots, deliberation of substantial facts through a variety of collective socio-economic as well as environmental perspectives, and suggestive measures will assist law enforcement officials, practitioners, and policymakers in adopting immediate, effective measures. Advanced GIS and Crime Analysis will be beneficial for students of criminology, research scholars, practitioners, urban planners, and policymakers to understand the complex crime patterns that exist in West Bengal"--